Analisis Faktor-Faktor Perkembangan UMKM Dengan Memanfaatkan Media Sosial Sebagai Media Promosi Untuk Meningkatkan Volume Penjualan - Sari, Adetia Novita; Nusantoro, Jawoto; Darmayanti, Elmira Febri (Universitas Muhammadiyah Metro, 2022)
This research is a qualitative research with a qualitative descriptive method which aims to determine the development of UMKM in Bandar Sribhawono District, to find out the use of social media as a promotional media by UMKM, and to find out that social media can increase sales volume. Data collection in the study used three techniques, namely: interviews, observation, and documentation. These three techniques are used to complement other data so that the data collected is truly valid. Data analysis uses inductive qualitative data analysis consisting of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the development of UMKM in Bandar Sribhawono, East Lampung, that the income of UMKM business actors fluctuates and tends to increase after using social media. In addition, the number of employees, product sales, and the number of consumers in business actors also increased. The use of social media can reach more consumers so this can increase sales and revenue